World production and trading in the commodities of forest industry - Yakobchuk , Valentyna (Forestry, Forest, Paper and Woodworking Industry, 2007)
The article presents the whole image of forest industry in the world, gives information about analysis and contemporary tendencies. Forest products is in demand nowadays that is the factor that determines this field of industry.